(untitled) (Journal of Surgical Sciences, 2021)
Background: Biliary bypass surgical procedures are the better options to restore the continuity of biliary system in patients with benign and or malignant extrahepatic biliary tract disorders including biliary tree injuries, obstruction and congenital anomalies. Over the past few decades, remarkable advances in surgical technology have been made that allow early recovery, better outcomes and more accurate treatment of biliary tract diseases. As a rule, biliary anastomoses, whether of duct to bowel or of duct to duct, heal very well provided that the principles of preservation of adequate blood supply, avoidance of tension, and accurate placement of sutures are followed. In preparing the bile duct for anastomosis, it is essential to define adequate margins while avoiding excessive dissection that might compromise the blood supply to the duct. Single-layer anastomoses have been constructed conventionally using an interrupted suture technique. It is however, increasingly popular to perform such anastomosis using a continuous suture. The quest for the best closure technique for biliary bypass surgery continues. The surgeon’s endeavour is to eliminate consequences of anastomosis failure: biliary leakage, peritonitis and dehiscence. There is a lack of consensus among surgeons over interrupted versus continuous suturing methods of biliary bypass surgery. Objectives: To make consensus about the suturing technique in biliary enteric bypass. Study design: Descriptive type of observational study. Study setting and period: Department of Surgery, Dhaka Medical College Hospital from January 2018 to December 2018. Journal of Surgical Sciences (2021) Vol. 25 (2 ): 22-30